The influence of nanotexturing of poly(lactic-co-glycolic acid) films upon human ovarian cancer cell attachment - Yaşayan, Gökçen; Xue, Xuan; Collier, Pamela; Clarke, Philip; Alexander, Morgan R.; Marlow, Maria (IOP Publishing, 2016)
In this study, we have produced nanotextured poly(lactic-co-glycolic acid) (PLGA) films by using polystyrene (PS) particles as a template to make a polydimethylsiloxane mould against which PLGA is solvent cast. Biocompatible, biodegradable and nanotextured PLGA films were prepared with PS particles of diameter of 57, 99, 210, and 280 nm that produced domes of the same dimension in the PLGA surface. The effect of the particulate monolayer templating method was investigated to enable preparation of the films with uniformly ordered surface nanodomes. Cell attachment of a human ovarian cancer cell line (OVCAR3) alone and co-cultured with mesenchymal stem cells (MSCs) was evaluated on flat and topographically nano-patterned surfaces. Cell numbers were observed to increase on the nanotextured surfaces compared to non-textured surfaces both with OVCAR3 cultures and OVCAR3-MSC co-cultures at 24 and 48 h time points.